Up-tapered fiber Mach-Zehnder interferometer fabricated by using a fusion splicer - 温晓东 宁提纲 油海东 李晶 冯亭 裴丽 简伟 (Optoelectronics letters, 2013)
An up-tapered Mach-Zehnder interferometer （MZI） is proposed and demonstrated. By applying a modification setting of an existing program of the fusion splicer, two up-tapers are fabricated by pushing both sides of the fiber to the middle. It is found that the maximum extinction ratio reaches up to 20 dB. With the fiber length of 6.3-49 cm between the two up-tapers, the free spectral range （FSR） changes from 10.7 nm to 1.3 nm. Besides, the wavelength of maximum extinction ratio shifts to the shorter wavelength in the scope of tens of nanometers, while the elongation changes from 0% to 0.23%.